Genetic counselling problems with parents of child with ROB der(21;21)(q10:q10) Down syndrome: a case report - Nisa. A.T. Hadi; Agustini Utari; Tri Indah Winarni (Faculty of Medicine, Universitas Trisakti, 2026)
BackgroundDown syndrome (DS) is a genetic disorder caused by addition of a full or partial chromosome 21. The most common type of DS (90–95%) is pure trisomy 21; mosaicism occurs in 6–7%, and about 3–5% comprises translocation DS including Robertsonian translocation, which could be inherited from parents. This case shows a Robertsonian translocation der(21;21)(q10:q10) DS and the common financial problem among Indonesian parents being their inability to pay for examinations to determine the origin of the abnormality (inherited or de novo), which is a big challenge for genetic counselors. Case DescriptionA 2-month-old baby boy was admitted to the hospital with suspect Down syndrome referred by a pediatrician. The patient was the only child of 25-year-old parents. Physical examination showed several characteristics of DS, including upslanting palpebral fissure, a flat nasal bridge, horizontal palmar creases, sandal gap, and continuous murmur in upper left sternal border due to patent ductus arteriosus. Cytogenetic testing revealed the karyotype of derivative chromosome 21, namely Robertsonian translocation 46,XY,+21,der(21;21)(q10:q10). Parents declined to order cytogenetic testing due to financial concerns. ConclusionParents’ karyotype is critical to confirm the origin of the translocation. It is important to calculate the recurrence risk correctly especially when parents still want another child and to do non-directive counseling in terms of reproductive options. However, it cannot be done in this case because of the lack of parent’s karyotypes. Genetic counseling plays an essential role in providing an accurate recurrence risk based on the type of trisomy for future offspring and reproductive planning.